Polyester opening master batch for biodegradable transparent film as well as preparation method and application of polyester opening master batch
By using ultrasonic dispersed nanosilicon dioxide as the opening agent in the preparation of biodegradable transparent films and adding 1,3-cyclohexadiate to reduce the crystallinity, the problem of uneven migration and dispersion of the opening agent in the prior art was solved, and film performance with high light transmittance, low haze and high biodecomposition rate was achieved.
Patent Information
- Application Number
- CN202510147682.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-11
AI Technical Summary
In the existing biodegradable transparent film preparation technology, the opening agent is easily migrated to the film surface, resulting in a decrease in light transmittance and haze, and the uneven dispersion of nano-silica affects the film performance.
Nanosilicon dioxide is used as the opening agent, and it is ultrasonic dispersed into a suspension in 1,4-butanediol before polymerization reaction and then added to the esterification kettle to ensure that it is dispersed uniformly. At the same time, 1,3-cyclohexadiate is added to reduce the crystallinity of the polyester open masterbatch and improve the light transmittance and haze of the film.
The uniform dispersion of nano-silicon dioxide in the film is achieved, which avoids its agglomeration and precipitation, improves the light transmittance and haze of the film, meets the requirements of materials for food packaging, and improves the biodegradation rate of the biodegradable transparent film.
Smart Images

Figure CN119955076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a polyester open masterbatch for a biodegradable transparent film and a preparation method and application thereof. Background Art
[0002] In the field of research and development and application of biodegradable materials, biodegradable transparent films have attracted much attention due to their environmentally friendly characteristics and wide application prospects. This type of film is mainly made of biodegradable materials such as PBAT and PLA as raw materials and is prepared through blending and modification technology. In order to improve the performance of the film, chain extenders are usually added to enhance the compatibility and melt strength of the material, and anti-blocking agents are also added to improve the smoothness and processing performance of the film.
[0003] However, there are some problems with the existing biodegradable transparent film preparation technology. On the one hand, when using organic opening agents, these opening agents are easy to migrate to the surface of the film, resulting in a hazy layer on the surface of the film, thereby reducing the light transmittance and haze of the film, affecting the appearance quality and application effect of the product. On the other hand, inorganic opening agents, especially nano-silicon dioxide, although they perform well in improving the smoothness of the film, are prone to agglomeration and uneven dispersion during the modified extrusion process due to the high viscosity of the raw materials, which also affects the light transmittance and haze of the film.
[0004] In order to solve these problems, researchers have conducted a lot of research and exploration. For example, patent CN115678214A proposes a high-stiffness, biodegradable, transparent functional masterbatch and its preparation method and application. The method prepares a masterbatch by blending and modifying high-mesh talcum powder, aluminum silicate and low-molecular weight polycaprolactone, and then cold-mixing and blowing film with PBAT. However, although this method improves the performance of the film to a certain extent, there are still some problems. For example, the organic component lubricant in the masterbatch will precipitate onto the surface of the film, affecting the light transmittance and haze of the film; at the same time, there are more powders in the masterbatch, which is difficult to disperse evenly, and also affects the overall performance of the film. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and provide a polyester open masterbatch for biodegradable transparent film and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing polyester open masterbatch for biodegradable transparent film comprises the following steps:
[0008] (a) adding terephthalic acid, 1,3-cyclohexanediol, 1,4-butanediol and catalyst a into an esterification reactor 1 to carry out an esterification reaction 1;
[0009] Adipic acid, 1,4-butanediol, nano-silicon dioxide suspension, and catalyst b are put into an esterification kettle 2 to perform an esterification reaction 2;
[0010] The dispersing medium of the nano-silicon dioxide suspension is 1,4-butanediol;
[0011] The molar ratio of the acid to the alcohol in the esterification reactor 1 is 1:1.5-2, the molar ratio of the acid to the alcohol other than the dispersion medium of the nano-silicon dioxide suspension in the esterification reactor 2 is 1:2-2.5, the temperature of the esterification reaction 1 is 210-230°C, and the temperature of the esterification reaction 2 is 170-200°C;
[0012] There is an excess of alcohol in both esterification reactor 1 and esterification reactor 2, the purpose is to allow the acid to react completely, and the excess alcohol that has not reacted during esterification can be pumped away during vacuuming; the reactivity of terephthalic acid is average, and the temperature of esterification reaction 1 is set in this way to shorten the reaction time; the reactivity of adipic acid is high, and the temperature of esterification reaction 2 is set in this way to avoid explosion caused by excessive temperature;
[0013] (b) The product of esterification reaction 1, the product of esterification reaction 2, the catalyst c, and the stabilizer are put into a polycondensation reaction kettle, and a preliminary polycondensation reaction and a final polycondensation reaction are carried out in sequence to obtain a polyester open masterbatch for a biodegradable transparent film.
[0014] The present invention uses nano silicon dioxide as an opening agent, which has the advantage of not migrating and precipitating, and can meet the requirements of food packaging materials; nano silicon dioxide has a spherical structure and a high specific surface area, which is conducive to the opening of the film and does not affect the printing of the film surface. The present invention adds nano silicon dioxide to 1,4-butanediol before the polymerization reaction, and ultrasonically disperses it into a nano silicon dioxide suspension and then adds it to the esterification kettle 2. On the one hand, because the reaction temperature of the esterification kettle 2 is relatively low, the nano silicon dioxide is not easy to explode. On the other hand, the amount of 1,4-butanediol added to the esterification kettle 2 is relatively large compared to the esterification kettle 1. At the same time, heating and stirring can make the nano silicon dioxide further dispersed evenly and reduce agglomeration.
[0015] In the present invention, 1,3-cyclohexanecarboxylic acid is added to the esterification reactor 1. The 1,3-cyclohexanecarboxylic acid can reduce the regularity of the molecular chain of the polyester open masterbatch, thereby reducing its crystallinity, making it a low-crystallization or non-crystalline material. At the same time, the 1,3-cyclohexanecarboxylic acid can also hinder the crystallization of PBAT when the polyester open masterbatch is blended with PBAT for film blowing, so that the overall crystallinity of the film is reduced, the light transmittance is increased, and the haze is reduced.
[0016] As the preferred technical solution:
[0017] In the method for preparing a polyester open masterbatch for a biodegradable transparent film as described above, in the esterification reactor 1, the molar ratio of terephthalic acid to 1,3-cyclohexanedicarboxylic acid is 1:0.2-0.5, and the molar ratio of catalyst a to acid is 1:800-1500; the time of the esterification reaction 1 is 2.5-4h, and the pressure is 50-80KPa.
[0018] According to the method for preparing a polyester open masterbatch for a biodegradable transparent film, in the esterification kettle 2, the molar ratio of acid to nano-silicon dioxide is 1:0.12-0.15, the molar ratio of catalyst b to acid is 1:1000-2000, and the nano-silicon dioxide suspension is obtained by mixing nano-silicon dioxide and 1,4-butanediol in a molar ratio of 1:5-7 and then ultrasonically dispersing for 4-6 hours; the time of the esterification reaction 2 is 2.5-4 hours, and the pressure is 50-80KPa.
[0019] In the method for preparing the polyester open masterbatch for biodegradable transparent film as described above, the ratio of the total molar amount of 1,3-cyclohexanedicarboxylic acid and terephthalic acid in the esterification kettle 1 to the molar amount of adipic acid in the esterification kettle 2 is 1:1.2.
[0020] In the method for preparing the polyester open masterbatch for biodegradable transparent film as described above, the ratio of the molar amount of catalyst c in the polycondensation reactor to the total molar amount of acid in the esterification reactor 1 and the esterification reactor 2 is 1:3600-6300, and the ratio of the molar amount of stabilizer in the polycondensation reactor to the total molar amount of acid in the esterification reactor 1 and the esterification reactor 2 is 1:3400-6000.
[0021] In the method for preparing the polyester open masterbatch for biodegradable transparent film as described above, the temperature of the preliminary polycondensation reaction is 215-240°C, the time is 3-6h, and the pressure is 5-40KPa; the temperature of the final polycondensation reaction is 215-245°C, the time is 4-6h, and the pressure is 80-200Pa.
[0022] In the method for preparing the polyester open masterbatch for biodegradable transparent film as described above, the catalyst a, catalyst b and catalyst c are each independently selected from one of tetrabutyl titanate and tetraethyl titanate, and the stabilizer is triphenyl phosphate or triethyl phosphate.
[0023] The present invention also provides a polyester open masterbatch for biodegradable transparent film, which is prepared by the preparation method of the polyester open masterbatch for biodegradable transparent film as described in any one of the above items, and contains a terephthalic acid-1,4-butanediol segment, a 1,3-cyclohexanediol-1,4-butanediol segment and adipic acid-1,4-butanediol segment in the molecular chain; the polyester open masterbatch for biodegradable transparent film has a melt index of 3.6-4.2 g / 10 min, a melting point of 100.52-112.7° C., an ash content of 1.86-2.36%, an L value of 75.4-83.9, an a value of -1.5-3.3, a b value of 4.2-7.9, and a crystallization enthalpy of 0.54-5.88 J / g.
[0024] The present invention also provides an application of the polyester open masterbatch for biodegradable transparent film as described above, which is used for blending with PBAT for film blowing to prepare a biodegradable transparent film.
[0025] As the preferred technical solution:
[0026] As described above, the content of PBAT in the biodegradable transparent film is 55-65wt%; the thickness of the biodegradable transparent film is 30-31μm, the transmittance is 89.3-90.5, the haze is 13.4-14.4, the opening is good, the film appearance is smooth and has no precipitation, and the biodegradability is 94.8-97.4%.
[0027] When the prior art uses an opening agent and PBAT to prepare a film, it is necessary to first granulate the opening agent and PBAT through a screw melt extrusion process, and then use the obtained particles (slices) for film blowing. When the present invention uses polyester opening masterbatch and PBAT to prepare a film, it is not necessary to first granulate the polyester opening masterbatch and PBAT through a screw melt extrusion process. The polyester opening masterbatch and PBAT are directly mixed evenly by a mixer and then blown film processing can be performed, which can avoid degradation caused by secondary processing and affect the service life of the product. The biodegradable transparent film obtained by the present invention has a high light transmittance and a low haze, which can meet the detection requirements of food film, and can be biodegraded at the same time, and the processing is simple and easy to operate, saving production costs.
[0028] Since 1,3-cyclohexanecarboxylic acid is introduced into the polyester open masterbatch, the molecular chain regularity of the polyester open masterbatch is reduced, the crystallinity of the polyester open masterbatch is reduced, and the content of benzene rings in the polyester open masterbatch is reduced. Therefore, the biodegradable transparent film containing a certain amount of the polyester open masterbatch is more easily decomposed by microorganisms under composting conditions, and the biodegradable transparent film has a high biodegradability.
[0029] Beneficial effects:
[0030] (1) The present invention uses nano-silicon dioxide as an opening agent, which has a spherical structure and a high specific surface area, which is conducive to the opening of the film. At the same time, the opening agent will not migrate and precipitate, which can meet the requirements of food packaging materials and ensure safety in use and performance stability.
[0031] (2) In the present invention, nano-silicon dioxide is dissolved in 1,4-butanediol solution before the polymerization reaction, ultrasonically dispersed into a nano-silicon dioxide suspension, and then added to the esterification kettle 2. The relatively low reaction temperature of the esterification kettle 2 can avoid the explosion of nano-silicon dioxide. In addition, the relatively large amount of 1,4-butanediol added in the kettle and the conditions of heating and stirring can be used to further disperse the nano-silicon dioxide evenly, reduce agglomeration, and ensure the uniformity of material performance.
[0032] (3) The present invention can reduce the regularity of the molecular chain of the polyester open masterbatch by adding 1,3-cyclohexanecarboxylic acid to the esterification reactor 1, thereby reducing its crystallinity to become a low-crystallization or non-crystalline material, and can hinder the crystallization of PBAT when it is blended with PBAT for film blowing, ultimately reducing the overall crystallinity of the film, increasing the light transmittance, and reducing the haze, thereby improving the optical properties and quality of the film.
[0033] (4) The biodegradable transparent film of the present invention is more easily decomposed by microorganisms under composting conditions, and the biodegradable transparent film has a high biodegradability rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is the DSC curve diagram of PBAT of Example 3;
[0035] Figure 2 This is the DSC curve of the polyester open masterbatch of Example 3. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0038] Melt index: tested according to GB / T 3682-2000 "Determination of mass flow rate and volume flow rate of thermoplastic melts"; the weight of the weight is 2.16kg and the temperature is set to 190℃.
[0039] Melting point and crystallization enthalpy: tested according to GB / T 19466.3-2004 "Plastics Differential Scanning Calorimetry (DSC) Part 3: Determination of Melting and Crystallization Temperature and Enthalpy" standard; wherein the starting temperature is 0°C, the ending temperature is 200°C, and the heating rate is 10°C / min (the test conditions for PBAT and polyester open masterbatch are the same).
[0040] Ash content: According to the provisions of GB / T 9345.1-2008 "Determination of ash content of plastics Part 1: General method", the direct combustion method (Method A) is adopted; wherein, the burning temperature is 850±50℃.
[0041] L value, a value, b value: tested according to 5.5.2 Method B (drying method) in GB / T 14190-2017 "Test method for fiber-grade polyester (PET) chips", using CIE1976L*a*b color system.
[0042] Haze, light transmittance: tested according to GB T 2410-2008 "Determination of light transmittance and haze of transparent plastics".
[0043] Opening property: If the film obtained after film blowing can be easily rubbed open by hand, it means that the opening property is good; if it cannot be rubbed open, it means that the opening property is poor.
[0044] Film appearance: Touch the film obtained after film blowing with your hand, and gently rub it to feel whether the film is smooth or rough; observe whether there are white crystalline fine particles on the surface of the film. If there are, it indicates that agglomerated nano-silicon dioxide has precipitated from the film (precipitation has occurred), and the dispersion is poor. If not, it indicates that non-agglomerated nano-silicon dioxide has precipitated from the film (no precipitation), and the dispersion is good.
[0045] Biodegradability: Tested in accordance with GB / T 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions - Determination of released carbon dioxide - Part 1: General method".
[0046] Example 1
[0047] A method for preparing a biodegradable transparent film, the specific steps are as follows:
[0048] (1) Preparation of raw materials;
[0049] Nano-silicon dioxide: average particle size is 30nm, whiteness is 98.8%;
[0050] Substance A, Substance B and Substance C: all are 1,4-butanediol;
[0051] Terephthalic acid;
[0052] 1,3-Cyclohexanedicarboxylic acid;
[0053] Catalyst a, catalyst b: both are tetrabutyl titanate;
[0054] Adipic acid;
[0055] Catalyst c: tetraethyl titanate;
[0056] Stabilizer: triphenyl phosphate;
[0057] PBAT: The manufacturer is Kanghui New Material Technology Co., Ltd., and the brand name is KHB21AP11;
[0058] (2) preparing nano-silicon dioxide suspension;
[0059] Nano-silicon dioxide and substance A were mixed at a molar ratio of 1:5 and then ultrasonically dispersed for 4 hours to obtain a nano-silicon dioxide suspension;
[0060] (3) preparing polyester open masterbatch;
[0061] (3.1) Terephthalic acid, 1,3-cyclohexanedicarboxylic acid, substance B, and catalyst a are placed in an esterification reactor 1, and the esterification reaction is carried out at a temperature of 210°C and a pressure of 50 KPa for 2.5 hours to obtain product 1. At the same time, adipic acid, substance C, nano-silica suspension, and catalyst b are placed in an esterification reactor 2, and the esterification reaction is carried out at a temperature of 170°C and a pressure of 50 KPa for 2.5 hours to obtain product 2;
[0062] In the esterification kettle 1, the molar ratio of the acid to the substance B is 1:1.5, the molar ratio of terephthalic acid to 1,3-cyclohexanediacid is 1:0.2, and the molar ratio of the catalyst a to the acid is 1:800; in the esterification kettle 2, the molar ratio of the acid to the substance C is 1:2, the molar ratio of the acid to nano-silica is 1:0.12, and the molar ratio of the catalyst b to the acid is 1:1000; the ratio of the total molar amount of 1,3-cyclohexanediacid and terephthalic acid in the esterification kettle 1 to the molar amount of adipic acid in the esterification kettle 2 is 1:1.2;
[0063] (3.2) After product 1, product 2, catalyst c and stabilizer are put into a polycondensation reactor, a pre-polycondensation reaction is first carried out at a temperature of 215° C. and a pressure of 5 KPa for 3 hours, and then a final polycondensation reaction is carried out at a temperature of 215° C. and a pressure of 80 Pa for 4 hours to obtain a polyester open masterbatch; wherein the ratio of the molar amount of catalyst c to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:3600, and the ratio of the molar amount of stabilizer to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:3400;
[0064] The prepared polyester open masterbatch has a melt index of 3.6 g / 10 min, a melting point of 112.7°C, an ash content of 1.86%, an L value of 83.9, an a value of -1.5, a b value of 4.2, and a crystallization enthalpy of 5.88 J / g.
[0065] (4) Preparation of biodegradable transparent films;
[0066] The polyester open masterbatch and PBAT are blended and blown into film to obtain a biodegradable transparent film; wherein, the relevant process parameters of the blended film blowing are: the first extrusion temperature is 140°C, the second extrusion temperature is 145°C, the third extrusion temperature is 145°C, the corner temperature is 145°C, the die body temperature is 145°C, the die mouth temperature is 145°C, the fan frequency is 35HZ, and the traction motor frequency is 11HZ.
[0067] The content of PBAT in the final biodegradable transparent film is 55wt%; the thickness of the biodegradable transparent film is 30μm, the transmittance is 89.8%, the haze is 13.7%, the opening is good, the film has a smooth appearance and no precipitation, and the biodegradability is 94.8%.
[0068] Example 2
[0069] A method for preparing a biodegradable transparent film, the specific steps are as follows:
[0070] (1) Preparation of raw materials;
[0071] Nano-silicon dioxide: average particle size is 30nm, whiteness is 98.8%;
[0072] Substance A, Substance B and Substance C: all are 1,4-butanediol;
[0073] Terephthalic acid;
[0074] 1,3-Cyclohexanedicarboxylic acid;
[0075] Catalyst a, catalyst b: both are tetrabutyl titanate;
[0076] Adipic acid;
[0077] Catalyst c: tetraethyl titanate;
[0078] Stabilizer: triethyl phosphate;
[0079] PBAT: The manufacturer is Kanghui New Material Technology Co., Ltd., and the brand name is KHB21AP11;
[0080] (2) preparing nano-silicon dioxide suspension;
[0081] Nano-silicon dioxide and substance A were mixed at a molar ratio of 1:7 and then ultrasonically dispersed for 6 hours to obtain a nano-silicon dioxide suspension;
[0082] (3) preparing polyester open masterbatch;
[0083] (3.1) Terephthalic acid, 1,3-cyclohexanedicarboxylic acid, substance B, and catalyst a are placed in an esterification reactor 1, and the esterification reaction is carried out at a temperature of 230°C and a pressure of 80 KPa for 4 hours to obtain product 1. At the same time, adipic acid, substance C, nano-silica suspension, and catalyst b are placed in an esterification reactor 2, and the esterification reaction is carried out at a temperature of 200°C and a pressure of 80 KPa for 4 hours to obtain product 2;
[0084] In the esterification kettle 1, the molar ratio of acid to substance B is 1:2, the molar ratio of terephthalic acid to 1,3-cyclohexanediacid is 1:0.35, and the molar ratio of catalyst a to acid is 1:1500; in the esterification kettle 2, the molar ratio of acid to substance C is 1:2.5, the molar ratio of acid to nano-silica is 1:0.15, and the molar ratio of catalyst b to acid is 1:2000; the ratio of the total molar amount of 1,3-cyclohexanediacid and terephthalic acid in the esterification kettle 1 to the molar amount of adipic acid in the esterification kettle 2 is 1:1.2;
[0085] (3.2) After product 1, product 2, catalyst c and stabilizer are put into a polycondensation reactor, a pre-polycondensation reaction is first carried out at a temperature of 240°C and a pressure of 40KPa for 6 hours, and then a final polycondensation reaction is carried out at a temperature of 245°C and a pressure of 200Pa for 6 hours to obtain a polyester open masterbatch; wherein the ratio of the molar amount of catalyst c to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:6300, and the ratio of the molar amount of stabilizer to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:6000;
[0086] The prepared polyester open masterbatch has a melt index of 4.2 g / 10 min, a melting point of 100.52°C, an ash content of 2.32%, an L value of 75.4, an a value of 3.3, a b value of 7.9, and a crystallization enthalpy of 0.54 J / g.
[0087] (4) Preparation of biodegradable transparent films;
[0088] The polyester open masterbatch and PBAT are blended and blown into film to obtain a biodegradable transparent film; wherein, the relevant process parameters of the blended film blowing are: the first extrusion temperature is 140°C, the second extrusion temperature is 145°C, the third extrusion temperature is 145°C, the corner temperature is 145°C, the die body temperature is 145°C, the die mouth temperature is 145°C, the fan frequency is 35HZ, and the traction motor frequency is 11HZ.
[0089] The content of PBAT in the final biodegradable transparent film is 65wt%; the thickness of the biodegradable transparent film is 31μm, the transmittance is 90.5%, the haze is 14.2%, the opening is good, the film has a smooth appearance and no precipitation, and the biodegradability is 97.4%.
[0090] Example 3
[0091] A method for preparing a biodegradable transparent film, the specific steps are as follows:
[0092] (1) Preparation of raw materials;
[0093] Nano-silicon dioxide: average particle size is 30nm, whiteness is 98.8%;
[0094] Substance A, Substance B and Substance C: all are 1,4-butanediol;
[0095] Terephthalic acid;
[0096] 1,3-Cyclohexanedicarboxylic acid;
[0097] Catalyst a, catalyst b: both are tetrabutyl titanate;
[0098] Adipic acid;
[0099] Catalyst c: tetraethyl titanate;
[0100] Stabilizer: triphenyl phosphate;
[0101] PBAT: The manufacturer is Kanghui New Material Technology Co., Ltd., the brand is KHB21AP11, and the DSC curve is as follows Figure 1 As shown;
[0102] (2) preparing nano-silicon dioxide suspension;
[0103] Nano-silicon dioxide and substance A were mixed at a molar ratio of 1:6 and then ultrasonically dispersed for 5 hours to obtain a nano-silicon dioxide suspension;
[0104] (3) preparing polyester open masterbatch;
[0105] (3.1) Terephthalic acid, 1,3-cyclohexanedicarboxylic acid, substance B, and catalyst a are placed in an esterification reactor 1, and the esterification reaction is carried out at a temperature of 220°C and a pressure of 65 KPa for 3.25 hours to obtain product 1. At the same time, adipic acid, substance C, nano-silica suspension, and catalyst b are placed in an esterification reactor 2, and the esterification reaction is carried out at a temperature of 185°C and a pressure of 65 KPa for 3.25 hours to obtain product 2;
[0106] In the esterification kettle 1, the molar ratio of acid to substance B is 1:1.75, the molar ratio of terephthalic acid to 1,3-cyclohexanediacid is 1:0.28, and the molar ratio of catalyst a to acid is 1:1200; in the esterification kettle 2, the molar ratio of acid to substance C is 1:2.25, the molar ratio of acid to nano-silica is 1:0.135, and the molar ratio of catalyst b to acid is 1:1500; the ratio of the total molar amount of 1,3-cyclohexanediacid and terephthalic acid in the esterification kettle 1 to the molar amount of adipic acid in the esterification kettle 2 is 1:1.2;
[0107] (3.2) After product 1, product 2, catalyst c and stabilizer are put into a polycondensation reactor, a pre-polycondensation reaction is first carried out at a temperature of 227° C. and a pressure of 22.5 KPa for 4.5 hours, and then a final polycondensation reaction is carried out at a temperature of 230° C. and a pressure of 140 Pa for 5 hours to obtain a polyester open masterbatch; wherein the ratio of the molar amount of catalyst c to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:4950, and the ratio of the molar amount of stabilizer to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:4700;
[0108] The obtained polyester open masterbatch has a melt index of 3.8 g / 10 min and a melting point of 104.78 ° C (DSC curve as shown in Figure 2 As shown), the ash content is 2.1%, the L value is 78.6, the a value is 1.3, the b value is 6.5, and the crystallization enthalpy is 2.34 J / g;
[0109] (4) Preparation of biodegradable transparent films;
[0110] The polyester open masterbatch and PBAT are blended and blown into film to obtain a biodegradable transparent film; wherein, the relevant process parameters of the blended film blowing are: the first extrusion temperature is 140°C, the second extrusion temperature is 145°C, the third extrusion temperature is 145°C, the corner temperature is 145°C, the die body temperature is 145°C, the die mouth temperature is 145°C, the fan frequency is 35HZ, and the traction motor frequency is 11HZ.
[0111] The content of PBAT in the final biodegradable transparent film is 60wt%; the thickness of the biodegradable transparent film is 30μm, the transmittance is 90.1%, the haze is 13.5%, the opening is good, the film has a smooth appearance and no precipitation, and the biodegradability is 96.7%.
[0112] Comparative Example 1
[0113] A method for preparing a thin film is basically the same as that in Example 3, except that the nano-silicon dioxide and substance A are directly put into the esterification kettle 2 without being mixed and ultrasonically dispersed before the two are put into the esterification kettle 2.
[0114] The transmittance of the film finally obtained was 83.5%, the haze was 23.5%, the film had a rough appearance, and white crystalline fine particles were precipitated.
[0115] Compared with Example 3, the light transmittance, haze and appearance of the film of Comparative Example 1 are significantly deteriorated. This is because in Comparative Example 1, the nano-silicon dioxide is not ultrasonically dispersed into a suspension, but is directly added to the esterification kettle 2. In the subsequent reaction process of the esterification kettle 2, the dispersion effect of the nano-silicon dioxide is poor, resulting in incomplete dispersion and agglomeration of nano-silicon dioxide particles. After film blowing, some particles precipitate and gather on the surface of the film, resulting in a rough appearance of the film. When light irradiates the film, the particles gathered on the surface of the film will hinder the passage of transmitted light, and at the same time, the amount of scattered light increases, resulting in a decrease in light transmittance and a large haze of the film.
[0116] Comparative Example 2
[0117] A method for preparing a thin film is basically the same as in Example 3, except that the nano-silicon dioxide suspension is not added into the esterification kettle 2 but into the esterification kettle 1 (the molar amount added is the same as in Example 3).
[0118] The transmittance of the film finally obtained was 84.6%, the haze was 22.7%, the film had a rough appearance, and white crystalline fine particles were precipitated.
[0119] Compared with Example 3, the light transmittance, haze and appearance of the film of Comparative Example 2 are significantly deteriorated. This is because the nano-silica suspension is added to the esterification kettle 1, and the amount of 1,4-butanediol added is lower than that of the esterification kettle 2, which makes it difficult to disperse the nano-silica well, and it is easy to agglomerate the nano-silica particles. At the same time, the reaction temperature of the esterification kettle 1 is 220°C. The temperature is relatively high, and it is easy to explode, making it more difficult for the nano-silica to be evenly dispersed in the polymer during the polymerization process; after the film is blown, some particles precipitate and gather on the surface of the film, resulting in a rough appearance of the film, and when light irradiates the film, the particles gathered on the surface of the film will hinder the passage of transmitted light, and at the same time, the amount of scattered light increases, resulting in a decrease in light transmittance and a large haze of the film.
[0120] Comparative Example 3
[0121] A method for preparing a film is basically the same as that of Example 3, except that 1,3-cyclohexanedicarboxylic acid is replaced with an equal molar amount of terephthalic acid.
[0122] The transmittance of the film finally obtained was 87.5% and the haze was 18.3%.
[0123] Compared with Example 3, the light transmittance and haze of the film in Comparative Example 3 are significantly deteriorated. This is because after replacing 1,3-cyclohexanedicarboxylic acid with terephthalic acid, the component that can reduce the regularity of the molecular chain of the polyester open masterbatch is lacking, which makes the crystallinity of the polyester open masterbatch relatively increased. Crystallization will cause more scattering of light inside the film, so the light transmittance of the film is reduced and the haze is increased.
[0124] Example 4
[0125] A method for preparing a biodegradable transparent film, the specific steps are as follows:
[0126] (1) Preparation of raw materials;
[0127] Nano-silicon dioxide: average particle size is 30nm, whiteness is 98.8%;
[0128] Substance A, Substance B and Substance C: all are 1,4-butanediol;
[0129] Terephthalic acid;
[0130] 1,3-Cyclohexanedicarboxylic acid;
[0131] Catalyst a, catalyst b: both are tetrabutyl titanate;
[0132] Adipic acid;
[0133] Catalyst c: tetraethyl titanate;
[0134] Stabilizer: triphenyl phosphate;
[0135] PBAT: The manufacturer is Kanghui New Material Technology Co., Ltd., and the brand name is KHB21AP11;
[0136] (2) preparing nano-silicon dioxide suspension;
[0137] Nano-silicon dioxide and substance A were mixed at a molar ratio of 1:6 and then ultrasonically dispersed for 5 hours to obtain a nano-silicon dioxide suspension;
[0138] (3) preparing polyester open masterbatch;
[0139] (3.1) Terephthalic acid, 1,3-cyclohexanedicarboxylic acid, substance B, and catalyst a are placed in an esterification reactor 1, and the esterification reaction is carried out at a temperature of 220°C and a pressure of 65 KPa for 3.25 hours to obtain product 1. At the same time, adipic acid, substance C, nano-silica suspension, and catalyst b are placed in an esterification reactor 2, and the esterification reaction is carried out at a temperature of 185°C and a pressure of 65 KPa for 3.25 hours to obtain product 2;
[0140] In the esterification reactor 1, the molar ratio of acid to substance B is 1:1.75, the molar ratio of terephthalic acid to 1,3-cyclohexanediacid is 1:0.35, and the molar ratio of catalyst a to acid is 1:1200; in the esterification reactor 2, the molar ratio of acid to substance C is 1:2.25, the molar ratio of acid to nano-silica is 1:0.135, and the molar ratio of catalyst b to acid is 1:1500; the ratio of the total molar amount of 1,3-cyclohexanediacid and terephthalic acid in the esterification reactor 1 to the molar amount of adipic acid in the esterification reactor 2 is 1:1.2;
[0141] (3.2) After product 1, product 2, catalyst c and stabilizer are put into a polycondensation reactor, a pre-polycondensation reaction is first carried out at a temperature of 227° C. and a pressure of 22.5 KPa for 4.5 hours, and then a final polycondensation reaction is carried out at a temperature of 230° C. and a pressure of 140 Pa for 5 hours to obtain a polyester open masterbatch; wherein the ratio of the molar amount of catalyst c to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:4950, and the ratio of the molar amount of stabilizer to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:4700;
[0142] The prepared polyester open masterbatch has a melt index of 3.9 g / 10 min, a melting point of 101.55°C, an ash content of 2.15%, an L value of 78.4, an a value of 1.2, a b value of 6.4, and a crystallization enthalpy of 0.68 J / g.
[0143] (4) Preparation of biodegradable transparent films;
[0144] The polyester open masterbatch and PBAT are blended and blown into film to obtain a biodegradable transparent film; wherein, the relevant process parameters of the blended film blowing are: the first extrusion temperature is 140°C, the second extrusion temperature is 145°C, the third extrusion temperature is 145°C, the corner temperature is 145°C, the die body temperature is 145°C, the die mouth temperature is 145°C, the fan frequency is 35HZ, and the traction motor frequency is 11HZ.
[0145] The content of PBAT in the final biodegradable transparent film is 60wt%; the thickness of the biodegradable transparent film is 31μm, the transmittance is 89.3%, the haze is 13.4%, the opening is good, the film appearance is smooth and has no precipitation, and the biodegradability is 96.5%.
[0146] Example 5
[0147] A method for preparing a biodegradable transparent film, the specific steps are as follows:
[0148] (1) Preparation of raw materials;
[0149] Nano-silicon dioxide: average particle size is 30nm, whiteness is 98.8%;
[0150] Substance A, Substance B and Substance C: all are 1,4-butanediol;
[0151] Terephthalic acid;
[0152] 1,3-Cyclohexanedicarboxylic acid;
[0153] Catalyst a, catalyst b: both are tetrabutyl titanate;
[0154] Adipic acid;
[0155] Catalyst c: tetraethyl titanate;
[0156] Stabilizer: triphenyl phosphate;
[0157] PBAT: The manufacturer is Kanghui New Material Technology Co., Ltd., and the brand name is KHB21AP11;
[0158] (2) preparing nano-silicon dioxide suspension;
[0159] Nano-silicon dioxide and substance A were mixed at a molar ratio of 1:6 and then ultrasonically dispersed for 5 hours to obtain a nano-silicon dioxide suspension;
[0160] (3) preparing polyester open masterbatch;
[0161] (3.1) Terephthalic acid, 1,3-cyclohexanedicarboxylic acid, substance B, and catalyst a are placed in an esterification reactor 1, and the esterification reaction is carried out at a temperature of 220°C and a pressure of 65 KPa for 3.25 hours to obtain product 1. At the same time, adipic acid, substance C, nano-silica suspension, and catalyst b are placed in an esterification reactor 2, and the esterification reaction is carried out at a temperature of 185°C and a pressure of 65 KPa for 3.25 hours to obtain product 2;
[0162] In the esterification kettle 1, the molar ratio of acid to substance B is 1:1.75, the molar ratio of terephthalic acid to 1,3-cyclohexanediacid is 1:0.28, and the molar ratio of catalyst a to acid is 1:1200; in the esterification kettle 2, the molar ratio of acid to substance C is 1:2.25, the molar ratio of acid to nano-silica is 1:0.15, and the molar ratio of catalyst b to acid is 1:1500; the ratio of the total molar amount of 1,3-cyclohexanediacid and terephthalic acid in the esterification kettle 1 to the molar amount of adipic acid in the esterification kettle 2 is 1:1.2;
[0163] (3.2) After product 1, product 2, catalyst c and stabilizer are put into a polycondensation reactor, a pre-polycondensation reaction is first carried out at a temperature of 227° C. and a pressure of 22.5 KPa for 4.5 hours, and then a final polycondensation reaction is carried out at a temperature of 230° C. and a pressure of 140 Pa for 5 hours to obtain a polyester open masterbatch; wherein the ratio of the molar amount of catalyst c to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:4950, and the ratio of the molar amount of stabilizer to the total molar amount of acid in esterification reactor 1 and esterification reactor 2 is 1:4700;
[0164] The prepared polyester open masterbatch has a melt index of 4.1 g / 10 min, a melting point of 105.24°C, an ash content of 2.36%, an L value of 78.8, an a value of 1.3, a b value of 6.6, and a crystallization enthalpy of 2.84 J / g.
[0165] (4) Preparation of biodegradable transparent films;
[0166] The polyester open masterbatch and PBAT are blended and blown into film to obtain a biodegradable transparent film; wherein, the relevant process parameters of the blended film blowing are: the first extrusion temperature is 140°C, the second extrusion temperature is 145°C, the third extrusion temperature is 145°C, the corner temperature is 145°C, the die body temperature is 145°C, the die mouth temperature is 145°C, the fan frequency is 35HZ, and the traction motor frequency is 11HZ.
[0167] The content of PBAT in the final biodegradable transparent film is 60wt%; the thickness of the biodegradable transparent film is 30μm, the transmittance is 89.9%, the haze is 14.4%, the opening is good, the film has a smooth appearance and no precipitation, and the biodegradability is 96.3%.
Claims
1. A method for preparing polyester open masterbatch for biodegradable transparent film, characterized in that: The following steps are involved: (a) adding terephthalic acid, 1,3-cyclohexanediol, 1,4-butanediol and catalyst a into an esterification reactor 1 to carry out an esterification reaction 1; Adipic acid, 1,4-butanediol, nano-silicon dioxide suspension, and catalyst b are put into an esterification kettle 2 to perform an esterification reaction 2; The dispersing medium of the nano-silicon dioxide suspension is 1,4-butanediol; The molar ratio of the acid to the alcohol in the esterification reactor 1 is 1:1.5-2, the molar ratio of the acid to the alcohol other than the dispersion medium of the nano-silicon dioxide suspension in the esterification reactor 2 is 1:2-2.5, the temperature of the esterification reaction 1 is 210-230°C, and the temperature of the esterification reaction 2 is 170-200°C; (b) The product of esterification reaction 1, the product of esterification reaction 2, the catalyst c, and the stabilizer are put into a polycondensation reaction kettle, and a preliminary polycondensation reaction and a final polycondensation reaction are carried out in sequence to obtain a polyester open masterbatch for a biodegradable transparent film.
2. The method for preparing a polyester open masterbatch for biodegradable transparent film according to claim 1, characterized in that: In the esterification reactor 1, the molar ratio of terephthalic acid to 1,3-cyclohexanedicarboxylic acid is 1:0.2-0.5, and the molar ratio of catalyst a to acid is 1:800-1500; the time of the esterification reaction 1 is 2.5-4h, and the pressure is 50-80KPa.
3. The method for preparing a polyester open masterbatch for biodegradable transparent film according to claim 1, characterized in that: In the esterification reactor 2, the molar ratio of acid to nano-silicon dioxide is 1:0.12-0.15, the molar ratio of catalyst b to acid is 1:1000-2000, and the nano-silicon dioxide suspension is obtained by mixing nano-silicon dioxide and 1,4-butanediol in a molar ratio of 1:5-7 and then ultrasonically dispersing for 4-6 hours; the time of esterification reaction 2 is 2.5-4 hours, and the pressure is 50-80KPa.
4. The method for preparing a polyester open masterbatch for biodegradable transparent film according to claim 1, characterized in that: The ratio of the total molar amount of 1,3-cyclohexanedicarboxylic acid and terephthalic acid in the esterification reactor 1 to the molar amount of adipic acid in the esterification reactor 2 is 1:1.
2.
5. The method for preparing a polyester open masterbatch for biodegradable transparent film according to claim 1, characterized in that: The molar ratio of the catalyst c in the polycondensation reactor to the total molar ratio of the acid in the esterification reactor 1 and the esterification reactor 2 is 1:3600-6300, and the molar ratio of the stabilizer in the polycondensation reactor to the total molar ratio of the acid in the esterification reactor 1 and the esterification reactor 2 is 1:3400-6000.
6. The method for preparing a polyester open masterbatch for biodegradable transparent film according to claim 1, characterized in that: The temperature of the preliminary polycondensation reaction is 215-240°C, the time is 3-6h, and the pressure is 5-40KPa; the temperature of the final polycondensation reaction is 215-245°C, the time is 4-6h, and the pressure is 80-200Pa.
7. The method for preparing a polyester open masterbatch for biodegradable transparent film according to claim 1, characterized in that: Catalyst a, catalyst b and catalyst c are each independently selected from one of tetrabutyl titanate and tetraethyl titanate, and the stabilizer is triphenyl phosphate or triethyl phosphate.
8. A polyester open masterbatch for biodegradable transparent film, characterized in that: The method for preparing a polyester open masterbatch for biodegradable transparent film as claimed in any one of claims 1 to 7 is adopted; the polyester open masterbatch for biodegradable transparent film has a melt index of 3.6-4.2 g / 10 min, a melting point of 100.52-112.7° C., an ash content of 1.86-2.36%, an L value of 75.4-83.9, an a value of -1.5-3.3, a b value of 4.2-7.9, and a crystallization enthalpy of 0.54-5.88 J / g.
9. The use of a polyester open masterbatch for biodegradable transparent film as claimed in claim 8, characterized in that: Used for blending with PBAT for film blowing to produce biodegradable transparent films.
10. The use according to claim 9, characterized in that: The content of PBAT in the biodegradable transparent film is 55-65wt%; the thickness of the biodegradable transparent film is 30-31μm, the transmittance is 89.3-90.5, the haze is 13.4-14.4, the opening is good, the film appearance is smooth and has no precipitation, and the biodegradability is 94.8-97.4%.
Citation Information
Patent Citations
Block copolyester as well as preparation method and application thereof
CN115725060A
Polyester resin, polyester resin composition, and sheet, film and hollow molded container obtained therefrom
CN1708531A
Polyester film having high light transmittance and method for manufacturing same
WO2023165112A1